Analisis Materi Struktur Atom pada Buku Kimia Kelas X Berdasarkan Kriteria Tahap Seleksi 4S TMD - Wahyuni, Roselina; Hadeli L, M. (LPPM Universitas Negeri Jakarta, 2022)
This study aims to determine achievement of 4S TMD selection criteria for atomic structure material in 2 SMA/MA chemistry textbooks (publishers YW and WJL) that most widely used in Ogan Ilir Regency. This type of research is descriptive qualitative with content analysis method. The 4S TMD selection stage, namely conformity to demands of the 2013 curriculum revision, correctness of concepts and inculcation of values. Concept suitability analysis is obtained by examining breadth and depth of the concept. The results of breadth concepts analysis in research object A obtained 18 appropriate concepts and 6 too broad concepts. Meanwhile, the breadth concepts in research object B obtained 18 appropriate concepts and 3 concepts are too broad. Then, results of depth concept analysis in research object A and research object B obtained 18 appropriate concepts. The results of the analysis of the truth of the concepts in research object A and research object B obtained 18 appropriate concepts in the atomic structure material are scientifically correct. The results of embedded value analysis in research object A obtained 10 embedded values. Meanwhile, results of embedded value analysis in research object B obtained 12 embedded values. From the results of the study, the researcher recommend WJL published chemistry textbook use in learning activities. Keywords: Textbook, Atomic Structure, 4S TMD